2019
DOI: 10.3892/etm.2019.8348
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑873 serves a critical role in human cervical cancer proliferation and metastasis via regulating glioma‑associated oncogene homolog 1

Abstract: Cervical cancer is a common gynecological malignancy with high morbidity worldwide. MicroRNAs (miRNAs) serve critical roles in cervical cancer progression. Accumulating evidence indicates that miR-873 functions as a tumor suppressor in certain types of cancer. However, the function and mechanism of miR-873 in the progression of cervical cancer have not been completely elucidated. In the present study, the role and mechanism of miR-873 in the proliferation, migration and invasion of cervical cancer cells were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…20 MiR-873 can suppress the viability of CC cells, thus retarding the development of CC. 21 In addition, miR-128 has been reported to play an anti-cancer role in CC. 22 A recent study has showed that up-regulation of miR-128 conspicuously inhibits the cell viability and epithelial-mesenchymal transition (EMT) procession in CC.…”
Section: Introductionmentioning
confidence: 99%
“…20 MiR-873 can suppress the viability of CC cells, thus retarding the development of CC. 21 In addition, miR-128 has been reported to play an anti-cancer role in CC. 22 A recent study has showed that up-regulation of miR-128 conspicuously inhibits the cell viability and epithelial-mesenchymal transition (EMT) procession in CC.…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatics analysis revealed a total of 22 miRNAs that were capable of complementary base pairing with LINC01426 ( Figure 3C ). Among these candidates, miR-519d-5p, 29 miR-873-3p, 30 , 31 miR-377-5p, 32 , 33 and miR-548c-3p 34 , 35 were selected for experimental verification because they played critical functions in various human cancers.
Figure 3 LINC01426 is a molecular sponge for miR-519d-5p in NSCLC cells.
…”
Section: Resultsmentioning
confidence: 99%
“…Among them, miR-873-5p is up-regulated in 4 types of cancers, including NSCLC ( 4 ), lung adenocarcinoma (LUAD) ( 28 , 29 ), lung cancer (LCA) ( 5 , 8 , 30 ), and Merkel cell carcinoma (MCC) (24627810). miR-873-5p is down-regulated in 14 types of cancers, including nasopharyngeal carcinoma (NPC) ( 32 ), lung cancer (LCA) ( 33 ), cervical cancer (CC) ( 34 , 35 ), EC ( 36 ), BC ( 10 , 11 , 37 , 38 ), pancreatic ductal adenocarcinoma (PDAC) ( 39 ), glioblastoma (GM) ( 9 , 40 42 ), osteosarcoma (OS) ( 43 ), papillary thyroid carcinoma(PTC) ( 44 ), CRC ( 6 , 45 49 ), esophageal cancer(ESCA) ( 50 ),GC ( 7 , 51 , 52 ), tongue squamous cell carcinoma (TSCC) ( 53 ), and pancreatic cancer(PC) ( 54 ).…”
Section: Mir-873-5p Dysregulation In Various Cancersmentioning
confidence: 99%
“…GLI1 is a transcription factor of the Hh signaling pathway and downstream target genes and is usually used as a marker to activate the Hh signaling pathway ( 80 ). Studies have found that increased expression of miR-873-5p can inhibit the expression of GLI1 and inhibit the cell proliferation of NSCLC ( 4 ), GC ( 51 ), and CC ( 35 ) through the Hh signaling pathway. STRA6, as a transmembrane protein of RA, is overexpressed in many cancer types ( 81 ).…”
Section: The Biological Role Of Mir-873-5p In Human Cancermentioning
confidence: 99%
See 1 more Smart Citation